Fraseologismi e lingua della politica. Considerazioni sull’esempio dei post di alcuni partiti tedeschi e italiani (PHRASIS | Rivista di studi fraseologici e paremiologici, 2019)
In the multimedia age the post published on social media becomes an efficient and powerful medium that some parties use to present and support their ideas in the attempt to appeal to voters and hold their attention. Moreover, the use of phrasemes, including slogans, proverbs, quotations etc., aims to impress voters by focusing attention on the emotional aspects of the discourse. Because of the immediacy and intelligibility of such phrases, they ensure clear communication between sender and recipient. The aim of this study is to describe some of the functions that idiomatic phrasemes perform in such multimedia texts, focusing in particular on the role they play in the text organization and in the creation of a contact with the reader. The analysis is carried out on a bilingual German-Italian corpus consisting of the posts of the main German and Italian political parties on the occasion of the federal elections in Germany on September 24th, 2017 and of the Italian general elections on March 4th, 2018.
Keywords: phrasemes, political language, persuasion strategies, social media